2012
DOI: 10.1111/jai.12018
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of Prochilodus argenteus Agassiz, 1829 (Pisces: Prochilodontidae) in São Francisco River, Brazil

Abstract: Summary Knowledge of the main reproductive parameters of a species is fundamental for comprehension of the reproductive behavior of a species within its habitat. To evaluate the reproductive biology of curimbatá, Prochilodus argenteus, an important species for commercial fisheries of the São Francisco River basin, Brazil, 153 females and 174 males were captured during 1999–2000 in the São Francisco River. The females (maximum total length 71.2 cm and maximum weight 7.8 kg) were larger than the males (65.0 cm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Based on the microscopic characteristics of the gonads, the maturation stages for females and males were determined (Weber et al., ). Fish size at first gonadal maturation was established based on the total length of the smallest female and male specimen in the spawned and spermiated stages, respectively, similar to the procedures used by Boncompagni‐Júnior, Normando, Brito, and Bazzoli ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the microscopic characteristics of the gonads, the maturation stages for females and males were determined (Weber et al., ). Fish size at first gonadal maturation was established based on the total length of the smallest female and male specimen in the spawned and spermiated stages, respectively, similar to the procedures used by Boncompagni‐Júnior, Normando, Brito, and Bazzoli ().…”
Section: Methodsmentioning
confidence: 99%
“…Fish size at first gonadal maturation was established based on the total length of the smallest female and male specimen in the spawned and spermiated stages, respectively, similar to the procedures used by Boncompagni-Júnior, Normando, Brito, and Bazzoli (2013).…”
mentioning
confidence: 99%
“…Both are abundant migratory fish and considered important species for commercial fisheries (Sato et al , ). P. argenteus , known as Curimba, is a characin (Order Characiformes) that attains a total length of up to 71 cm and is endemic to the São Francisco River (Boncompagni‐Júnior et al , ). P. maculatus , known as the Mandi‐Amarelo, is a catfish (Order Siluriformes) with a total length of up to 44 cm and is widely distributed in South American rivers (Barbosa et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The GSI and HSI may vary among fish because of reproductive period (Boncompagni, Normando, Brito & Bazzoli ), differences in sensitivity to the exposure to contaminants (Pereira et al . ), and being kept in confinement (Honji et al .…”
Section: Discussionmentioning
confidence: 99%
“…The GSI and HSI may vary among fish because of reproductive period (Boncompagni, Normando, Brito & Bazzoli 2013), differences in sensitivity to the exposure to contaminants (Pereira et al 2012), and being kept in confinement (Honji et al 2009). Because of this, another common response in the livers of fish subject to poisoning is the diminishing reserves of liver glycogen (Glover et al 2007) due to hyperarousal (Pereira et al 2012) and shown by a decreased hepatosomatic index (Prado et al 2011), as observed in this study.…”
Section: Discussionmentioning
confidence: 99%